Influencia cultural del K-pop en jóvenes limeños - García Jiménez, Moisés Gustavo (2018)
K-pop culturally influences a sector of young people from Lima. This musical genre came more than ten years ago to our country and is part of the so-called «Korean Wave» or Hallyu, a Korean cultural movement that emerged in the late twentieth century and is now expanding worldwide.Through an ethnographic work and the application of qualitative and quantitative research techniques, for which a sample of 384 people was taken, it has been verified that there are positive values that are transmitted through K-pop and that Idols, that is to say, the Korean artists that spread this music, are considered individuals of reference and example to follow by their fans. However, despite the Korean cultural influence they receive from K-pop, these young Lima fans, who can also be called K-popers, would not change their Peruvian culture, but rather seek to forge their identity with positive values that they can acquire from another culture, in this case, from the Korean.